(untitled) (Journal of Geography and Environmental Management, 2021)
Urban development, urban population and the level of urbanization are one of the main indicators of the country’s development. The growth of the city’s population is influenced by its economic and socio-cultural base, opportunities for job creation, economic structure and the role of labor-intensive industries. In the Aran economic region, as elsewhere in the country, the decline in the activities of urban facilities in the first years of independence, the reduction of jobs, declining living standards and migration flows have had a negative impact on this process. Therefore, the level of urbanization in the country has remained unchanged for several decades. Implemented reforms still have a weak impact on this process. The article examines the problems in this area and develops proposals to address them. The article analyzes the dynamics of the level of urbanization in the Aran economic-geographical region, the formation and development of urban settlement in the administrative regions. The study of demographic processes in urban areas of the region shows that in recent years there has been a natural increase in the population, a decrease in the dynamics of births and marriages, an increase in mortality, infant mortality and divorce. The population potential and the current state of industrial production in the territory of the Aran economic-geographical region of Azerbaijan, both in the cities of the republican subordination and the central type of the administrative region, have been studied. The prospects of future development of the cities were commented by studying the issues of employment and use of labor resources in the Aran economic-geographical region. Establishment of joint (by attracting foreign investors) industrial enterprises in the Aran economic-geographical region, which can produce modern, competitive products based on full, complex processing of abundant agricultural raw materials, will improve the economic base and social infrastructure of the cities of the economic region. Development of agriculture and related processing industries, trade, services and other areas based on the economic potential of the Aran economic-geographical region will increase the level of employment and stimulate the population to remain in the field by providing jobs with increasing demographic potential. The article provides information on the socio-economic situation in the Aran economic-geographical region, is important for assessing the level of use of existing potential, attracting foreign and local investors to various sectors of the region’s economy. Azerbaijan, including the Aran economic and geographical region, has great potential for the non-oil sector of the economy. Cotton, grapes, grain, fruits and vegetables, potatoes, various cereals, etc. are grown in the fertile lands of the Aran zone of the republic. It is possible to significantly increase the volume and value of output as a result of the creation of Agrarian-Industrial Complexes by attracting investments in this area as well.